Response differences of two maize hybrid varieties to the application of bioagent-ameliorant and chicken manure in fertile soil - Kantikowati, Endang; Karya, Karya; Yusdian, Yudi; Minangsih, Dian Murti; Turmuktini, Tien; Yuliani, Erna; Faujiah, Fija (Universitas Padjadjaran, 2023)
To ensure adequate nutrition for the growth of maize (Zea mays L.) in sustainable agriculture, it is necessary to apply bio-agent soil conditioner and manure. This study aims to determine the effect of doses of bioagent-ameliorant and chicken manure on growth and yield components. The research was conducted in highland with an altitude 800 m above sea level. This study used an experimental method with two sets of experiments, namely experiments using one and two-cobs maize cultivars. The experiment used a randomized block design (RBD) with two treatment factors and three replications. The first treatment factor was the dose of bioagent ameliorant, which consisted of 3 levels, namely 0, 7.5, and 15 kg/ha, while the second factor was the dose of chicken manure, which consisted of 3 levels, namely 0.5 and 10 tons/ha. The observed growth components were plant height and number of leaves, while the yield components observed were cob length, cob diameter, cob weight per plant, and cob weight per plot. In research on two-cob maize experiment, there was no interaction effect between doses of soil conditioner and chicken manure, while the interaction effect on plant height occurred in one-cob maize experiment. The single effect of ameliorant doses could not increase all components of growth and yield, both in one and two-cob maize cultivars. The single effect of doses of chicken manure increased number of leaves, cob length, cob weight per plant, and cob weight per plot in one-cob maize cultivar, while increased plant height in two-cob maize cultivar.